Solid-liquid equilibrium measurements for the ternary system PCL + chloroform + nonsolvents (n-hexane, ethanol, methanol, isopropanol) at 303.15 K - doi: 10.4025/actascitechnol.v36i1.16615 - Albini, Loyse Tussolini; Cardozo-Filho, Lucio; Kunita, Marcos Hiroiuqui; Mafra, Marcos Rogerio; Corazza, Marcos Lucio (Acta Scientiarum. Technology, 2014)
This work reports experimental data of polycaprolactone (PCL) polymer solubility in chloroform as solvent and n-hexane, methanol, ethanol and isopropanol as nonsolvents, at atmospheric pressure (about 1,0 bar) and temperature of 303.15 K. It was used PCL with 70000-90000 and 2000 molar mass (MM). The experiments of solubility were performed using a jacketed-cell with temperature controlled by an ultrathermostatic bath, in which a turbidity method was adopted and used. From the obtained results it should be observed that the n-hexane presented a more pronounced anti-solvent effect in the PCL solubility, where the heterogeneous region (solid phase presence) was broader than when other nonsolvent. It was also observed that the binodal curves measured with the high molar mass polymer showed similar results compared to the low molar mass one. Â 